Pengembangan Perangkat Pembelajaran Model Inkuiri Terbimbing untuk Meningkatkan Hasil Belajar Fisika Peserta Didik. - Najwa Najwa; Gunawan Gunawan; Hairunnisyah Sahidu; Ahmad Harjono (Department of Physics Education, Universitas Mataram, 2022)
This development research aims to produce products in the form of learning tools with the guided inquiry model to improve students' cognitive learning outcomes of physics. This type of research is included in Research and Development (R&D) with a PPE model consisting of Planning, Production, and Evaluation. The learning device products developed are syllabus, Learning Implementation Plan, Student Worksheets, and Test Instruments. Data collection techniques used validation sheets. The data on the validity of the learning device was obtained from filling out the validation sheet by the validators and analyzed using a Likert scale. The results of the study based on the assessment of the validators showed that the average value of the overall validity of the learning tools developed was 3.05 to 3.70 with good and very good category. Based on the interpretation of the data, it can be concluded that the guided inquiry model is valid for use in learning.